Embarazo no deseado y fuentes de información impresas y audiovisuales, en mujeres peruanas (2004-2005) - Huamán-Calderón, Diana (2009)
Background: It is possible that there is a relationship between reading newspapers and magazines, watching televisión and ¡istening to the radio and unwanted pregnancies. Aim: To assess the relationship between the access to printed and audiovisual information resources and unwanted pregnancy in Peruvian women. Material and methods: A sample of 5,071 women, aged between 18 and 30 years was selected from a datábase of a Demographics and Health survey performed between 2004 and 2005. Using the information obtained in the survey, the association between unwanted pregnancies and reading newspapers and magazines, was analyzed. Results: Twenty six percent of women had at least an unwanted child (n =1,327). Radio and televisión were the media mostly used by these women. Seventy five percent of women almost never read newspapers and magazines. The lack of reading and the reliance in televisión and radio as sources of information were all associated with unwanted pregnancy (p & lt;0.001). Conclusions: In this sample of women, there is a negligible interest for reading and a high preference for radio and televisión. This explains the poor knowledge on sexual and reproductive health and the lack of impact of printed materials used in educational campaigns.